Zamanın A-B Serileri: Şimdinin Mahiyeti Üzerine Tartışmalar - Küçükparmak, Aykut (My University, 2016)
From the beginning, on the debate on issues related to the time and the nature of the time, has always been one of the most important and intricate problem areas of philosophy. Recently this debates' position in the philosophy has become more important with the impact of the developments in physics. In this period, the British idealist philosopher McTaggart's distinction of time's A - B series come at the beginning of the most important discussion topics in the literature of philosophy. A and B series refers to two separate approaches depicting differently the relationship scheme between events and the moments of the time. By arguing that this distinction is the two final form of time can be comprehend by human cognition, Mctaggart try to ground his thesis 'unreality of time'. On the other hand this distinction within the framework of the present time philosophy discussions; it has already been adopted as a generally accepted distinction independently with the the thesis of unreality of the time. At first in this regard throughout our work the features and differences of the time's A - B series will be revealed, secondly on the basis of this distinction different theories of time and reality that were put forward will be discussed
A-B Series of Time: Debates on the Nature of Present
Keywords: Felsefe